ANALISIS PERAN KOMISI UNTUK ORANG HILANG DAN KORBAN TINDAK KEKERASAN (KONTRAS) SEBAGAI CIVIL SOCIETY DALAM PENGUNGKAPAN KASUS PEMBUNUHAN MUNIR - Fahmi Nur Ichsan; Fitriyah .; Puji Astuti (Journal of Politic and Government Studies, 2014)
KontraS as civil society (organization) has done advocacies for Munir murder case for nine years. Any efforts have been done by using advocacy strategies such as case investigation, legal assistance, demonstration, and making opinion in mass media. But those efforts seem like hit a great wall: government's willing to handle and reveal Murnir murder case. KontraS's efforts should be continue to reveal Murnir murder case by keep the solidarity with other civil society. Then, KontraS should make issue expansion for Murnir murder case such as relating the case with human rights defender and ntelligent regulations draft to keep society to still remember for this case.Keywords: KontraS, civil society, Munir, human rights